The activists’ Shelter: Enabling activism through architecture - Boman, Ellen (My University, 2023)
The purpose of this Master’s Thesis within the subject of Architecture is to design and build a treehouse for climbing climate activists who wish to stay in them when carrying out blockades in forests as an action to protest against deforestation. The main finding from this thesis is that designers can - by being intentional with their actions, aware of design decisions and by being conscious about what they produce – angle what impact they have. I have chosen to enable activism through architecture because activists are at the frontline in the war between society as we know it, and a liveable planet in the future. There are three objectives to this thesis: 1. The act of designing this treehouse is a way to showcase how the designer can choose which impact her design will have. In the case of this thesis, designing a tool for activists to use. 2. Explore and challenge in writing the role of the architect in the aspect of climate action and activism. The thesis itself should be: provocative, empowering and informative both for the architect and the activist. 3. The impact the design will have for the environmental movement. The treehouse should be: reproduceable, materials should have minimal environmental impact, shelter two people from weather, wind and water cannons, be easy to set up for two people, be able to move to new locations (reusable), the design needs to fit a variety of types and size of tree. The design should enable smoother and longer forest blockades. The research methods used were a combination of participatory observation by, informal interviews and immersion with climbing climate activist, and literature research about the fields of knowledge surrounding architecture and activism, politics and climate, and lastly researching by designing and building. Presented in the form of a how-tohandbook is the final design proposal, as well as being built in scale 1:100 and 1:1.
Keywords: Activism; Architecture; Forestry; Treehouse; Treesit